Adaptabilidad y producción de dos variedades de maní (Arachis hypogaea l.) con dos abonos orgánicos en la parroquia Moraspungo - Caiza Puma, Jesus Carmela (2015)
In Moraspungo parish, the research was conducted in order to assess the adaptability and production of two varieties of peanut (Arachis hypogaea L.) with two organic fertilizers, with eight treatments five repetitions and five plants as experimental unit, the design was used randomized complete block (RCBD) factorial arrangement with two by four, being the factor A (peanut varieties) and B (organic fertilizer) factor, as for the best results of the research are as follows; in the variable plant height treating Rosita INIAP 381 variety - witness the harvest with 44.36 cm. In stem diameter in the treatment of rosette 381 + INIAP harvest poultry with 1.96 cm....